2017
DOI: 10.3126/nvj.v34i0.22859
|View full text |Cite
|
Sign up to set email alerts
|

Study of Antibiotic Resistance on Escherichia Coli in Commercial Poultry of Nepal

Abstract: The continuous use of antibiotics in compound feed at sub-therapeutic level has been an integral part of commercial poultry production in Nepal, which is one of the factors that promotes bacterial resistance. Hence, with the objective to determine antibiotic resistance in commercial poultry of Nepal, this study was designed taking Escherichia coli as a flagship bacterium. The commercial layers and broilers birds brought to veterinary teaching hospital of Agriculture and Forestry University by commercial poultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Antibiotic susceptibility profiles of E. coli in this study are consistent with previous studies reported from Bangladesh [47], the Netherlands [48] and Nepal [49]. While tetracycline was not in use as a treatment options against E. coli infections in poultry farms, high resistance seen towards this drug could be attributable to the misuse of tetracycline as growth promoters [46].…”
Section: Discussionsupporting
confidence: 89%
“…Antibiotic susceptibility profiles of E. coli in this study are consistent with previous studies reported from Bangladesh [47], the Netherlands [48] and Nepal [49]. While tetracycline was not in use as a treatment options against E. coli infections in poultry farms, high resistance seen towards this drug could be attributable to the misuse of tetracycline as growth promoters [46].…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, broilers had not developed this resistance. Resistance to amikacin was not detected in any of the samples [ 29 ]. The E. coli from broilers in our study showed resistance to gentamicin in 2.94% and to tobramycin in 1.96% of samples.…”
Section: Discussionmentioning
confidence: 99%
“…The AMR also has an impact on the sustainable development goals, particularly those that address hunger, poverty, malnutrition, health, and economic growth [ 59 ]. Multiple antibiotics, including the most R AP and tetracycline, were used for the treatment and prevention of bacterial poultry disease at suboptimal levels, which may be the main cause of the high resistance rates in veterinary practice in Nepal [ 60 ]. The previous study also supports the marked increase in veterinary antibiotic sales in Nepal [ 61 ] in the past few years.…”
Section: Discussionmentioning
confidence: 99%